PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis gueneensis Jacq) DI PEMBIBITAN UTAMA (MAIN NURSERY) PADA MEDIUM SUBSOIL ULTISOL YANG DIAPLIKASIKAN AMELIORAN ANORGANIK DAN ORGANIK - Fauzan Abadi; Nelvia Nelvia (DINAMIKA PERTANIAN, 2017)
The research aims to study the effect of inorganic and organic ameliorant dressing on ultisol subsoil medium on the growth of oil palm (Elaeis gueneensis Jacq)seedling in the main nursery. The research was conducted at greenhouse AgricultureFaculty, Riau University Pekanbaru from June to November 2016.The experiment in form factorial using Completely Randomized Design (CRD).The first-factor is an organic ameliorant ei.fly ash and dregs consist of 4 levels (without ameliorant, 50 g fly ash, 50 g dregs and 25 fly ash + 25 dregs per polybag). The second factor is organic ameliorant ei.cocopeat and oil palm empty fruit bunches compost (OPEFBC)consist of 6 levels (without ameliorant, 100 g cocopeat, 100 g OPEFBC, 50 g cocopeat + 50 g OPEFBC, 100 g cocopeat + 50 g OPEFBC and 50 g cocopeat + 100 g OPEFBC per polybag). The parameters observed were the addition of plant height, number of leaves, a diameter of the stump, length of leaf midrib and leaves. The results showed that the combination of 50 g dregs/polybag with 100 g OPEFBC/polybag increased the plant height and combination of 25 g fly ash + 25 g dregs with 50 g cocopeat + 50 OPEFBC increased diameter of stump and length of leaf midrib significantly compared to without ameliorant, but non significantly compared to another combination.